Development and validation of a subject-specific moving-axis tibiofemoral joint model using MRI and EOS imaging during a quasi-static lunge. (27th April 2018) - Dzialo, C.M.; Pedersen, P.H.; Simonsen, C.W.; Jensen, K.K.; de Zee, M.; Andersen, M.S.
Abstract: The aims of this study were to introduce and validate a novel computationally-efficient subject-specific tibiofemoral joint model. Subjects performed a quasi-static lunge while micro-dose radiation bi-planar X-rays (EOS Imaging, Paris, France) were captured at roughly 0°, 20°, 45°, 60°, and 90° of tibiofemoral flexion. Joint translations and rotations were extracted from this experimental data through 2D-to-3D bone reconstructions, using an iterative closest point optimization technique, and employed during model calibration and validation. Subject-specific moving-axis and hinge models for comparisons were constructed in the AnyBody Modeling System (AMS) from Magnetic Resonance Imaging (MRI)-extracted anatomical surfaces and compared against the experimental data. The tibiofemoral axis of the hinge model was defined between the epicondyles while the moving-axis model was defined based on two tibiofemoral flexion angles (0° and 90°) and the articulation modeled such that the tibiofemoral joint axis moved linearly between these two positions as a function of the tibiofemoral flexion. Outside this range, the joint axis was assumed to remain stationary. Overall, the secondary joint kinematics (ML: medial–lateral, AP: anterior-posterior, SI: superior-inferior, IE: internal-external, AA: adduction-abduction) were better approximated by the moving-axis model with mean differences and standard errors of (ML: −1.98 ± 0.37 mm, AP: 6.50 ± 0.82 mm, SI: 0.05 ± 0.20 mm, IE: 0.59 ± 0.36°, AA: 1.90 ± 0.79°) and higher coefficients of determination (R 2 ) for each clinical measure. While the hinge model achieved mean differences and standard errors of (ML: −0.84 ± 0.45 mm, AP: 10.11 ± 0.88 mm, SI: 0.66 ± 0.62 mm, IE: −3.17 ± 0.86°, AA: 11.60 ± 1.51°).